Comparative mapping of ESG greenwashing research between China and the global context: a CiteSpace-based bibliometric analysis - Hu, Ge; Xu, Ziteng; Chen, Weimin (Frontiers in Sustainability, 2026)
As Environmental, Social, and Governance (ESG) principles gain global traction, greenwashing has emerged as a significant challenge, undermining sustainable development and eroding trust in capital markets. This study provides a systematic review of ESG greenwashing research in both English and Chinese literature, conducting a bibliometric analysis of 652 papers published between 2017 and 2025. These papers were sourced from the Web of Science Core Collection and CNKI databases, using CiteSpace for visualization. The research timeline reveals three phases: the emerging phase (2017—2021), the growth phase (2022–2023), and the expansion phase (2024—2025), showing a consistent rise in research activity. Co-occurrence and clustering analyses of keywords reveal that English-language literature predominantly addresses green marketing, corporate social responsibility, and legitimacy, while Chinese-language research, emerging later, focuses on practical issues such as financing constraints, green finance, information disclosure, and collaborative governance. Future research should focus on AI governance, firm perception of institutional pressures, executive characteristics, and the coordination of policy instruments to address ESG greenwashing.